2014
DOI: 10.1590/0074-0276140231
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns, emm type distribution and genetic diversity of Streptococcus pyogenes recovered in Brazil

Abstract: Streptococcus pyogenes is responsible for a variety of infectious diseases and immunological complications. In this study, 91 isolates of S. pyogenes recovered from oropharynx secretions were submitted to antimicrobial susceptibility testing, emm typing and pulsed-field gel electrophoresis (PFGE) analysis. All isolates were susceptible to ceftriaxone, levofloxacin, penicillin G and vancomycin. Resistance to erythromycin and clindamycin was 15.4%, which is higher than previous reports from this area, while 20.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
4
12
1
Order By: Relevance
“…Amongst non-invasive infections, cluster E6 was the most abundant cluster. This is in accordance with previous reports completed by Sagar (40), Dhanda (41) and Arêas (42), that identified emm types belonging to cluster E6 (emm75, emm81) as the predominant isolates obtained from countries closely relating to the impoverished environments within Africa, India and Brazil respectively. However, when referring to invasive disease, the predominant emm clusters are E3, followed by E6 and D4, which is complimentary to the emm cluster data shown by Chiang-Ni (18).…”
Section: Discussionsupporting
confidence: 93%
“…Amongst non-invasive infections, cluster E6 was the most abundant cluster. This is in accordance with previous reports completed by Sagar (40), Dhanda (41) and Arêas (42), that identified emm types belonging to cluster E6 (emm75, emm81) as the predominant isolates obtained from countries closely relating to the impoverished environments within Africa, India and Brazil respectively. However, when referring to invasive disease, the predominant emm clusters are E3, followed by E6 and D4, which is complimentary to the emm cluster data shown by Chiang-Ni (18).…”
Section: Discussionsupporting
confidence: 93%
“…The M protein gene prevalence in GAS (93.3z) from this study was comparable to that (94.5z) reported in Brazil (16). A previous study in Thailand showed the predominant M protein type of GAS to be M93 (20.75z); other M types included M1, M44/61, and M25 (17).…”
supporting
confidence: 80%
“…[12] This may be related to the discontinued usage of tetracycline to treat streptococcal pharyngitis, and it was also reported to GAS isolates. [28] However, we do not have national data about tetracycline usage over the years to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 86%